Sistem Kendali Lampu Otomatis ESP8266 Berbasis Sensor PIR dan Monitoring Aplikasi Blynk - Adit Ramadan; Muhammad Ridwan Martana; Naaq Shal Ramadanu (Tech : Journal of Engineering Science, 2026)
Energy efficiency issues in building lighting sectors often stem from human negligence in turning off electronic devices, resulting in significant operational electricity costs. This research aims to design and implement a smart light control system based on the Internet of Things (IoT) using the ESP8266 microcontroller, HC-SR501 PIR sensor, and Blynk platform. The method used is experimental with a hardware design approach separating low and high current paths, alongside software development using non-blocking logic in Arduino IDE. Integration with the IoT platform allows dual control: automation based on motion detection and remote manual control via mobile application. Test results show the PIR sensor has a 100% detection accuracy rate at an optimal distance of up to 4 meters. Furthermore, efficiency analysis shows that this system implementation can reduce unnecessary active lamp duration, resulting in an average energy saving of ± 45.8% compared to manual systems. This study concludes that the combination of physical sensors and cloud-based control is a reliable and responsive solution to support energy conservation in modern buildings.